Mekanisme Monitoring, Bonding Dan Ukuran Perusahaan Pada Kinerja Perusahaan - Hidayat, Riskin; Rosita, Rosita; Susanto, Heri; Rachmawati, Ida Ayu Kade (Jurnal Bisnis dan Kewirausahaan, 2023)
This research aims to examine the influence of bonding and monitoring mechanisms, as well as firm size, on firm performance across various industries listed on the Indonesia Stock Exchange. The study population consists of 45 companies from diverse industries. The research sample was obtained using purposive sampling, resulting in a sample of 14 companies. The findings of the study indicate that institutional ownership and debt have a significant positive effect on firm financial performance. However, firm size does not have a significant negative impact on firm performance. In this context, bonding and monitoring mechanisms, as well as institutional ownership and debt levels, play a crucial role in enhancing the financial performance of companies in the Indonesian Stock Exchange. These findings provide insights for managers and stakeholders to consider appropriate ownership strategies and debt structures to improve firm performance. Furthermore, firm size is not considered a critical factor influencing firm performance in the context of this research.